Robber flies of South Korea-V. South Korean species of the Subfamily Apocleinae Papavero, 1973 (Diptera, Asilidae) - Young, Charles L.; Hradský, Milan M. (Zootaxa, 2008)
Two genera and 5 species within the subfamily Apocleinae Papavero, 1973 are recorded from South Korea. New records include: Philodicus integer (Macquart, 1846), Promachus anicius (Walker, 1849), Promachus chinensis Ricardo, 1920 and Promachus nigribarbatus (Becker, 1925). The genus Philodicus Loew is a new record for the area. Drawings of diagnostic features, a checklist, key and descriptions are included.